Acromioclavicular and sternoclavicular joint dislocations indicate severe concomitant thoracic and upper extremity injuries in severely injured patients - Bakir, M. Sinan; Lefering, Rolf; Haralambiev, Lyubomir; Kim, Simon; Ekkernkamp, Axel; Gümbel, Denis; Schulz-Drost, Stefan (Scientific Reports, 2020)
Preliminary studies show that clavicle fractures (CF) are known as an indicator in the severely injured for overall injury severity that are associated with relevant concomitant injuries in the thorax and upper extremity. In this regard, little data is available for the rarer injuries of the sternoclavicular and acromioclavicular joints (SCJ and ACJ, respectively). Our study will answer whether clavicular joint injuries (CJI), by analogy, have a similar relevance for the severely injured. We performed an analysis from the TraumaRegister DGU (TR-DGU). The inclusion criterion was an Injury Severity Score (ISS) of at least 16. In the TR-DGU, the CJI were registered as one entity. The CJI group was compared with the CF and control groups (those without any clavicular injuries). Concomitant injuries were distinguished using the Abbreviated Injury Scale according to their severity. The inclusion criteria were met by n = 114,595 patients. In the case of CJI, n = 1228 patients (1.1%) were found to be less severely injured than the controls in terms of overall injury severity. Compared to the CF group (n = 12,030; 10.5%) with higher ISS than the controls, CJI cannot be assumed as an indicator for a more severe trauma; however, CF can. Concomitant injuries were more common for severe thoracic and moderate upper extremity injuries than other body parts for CJI. This finding confirms our hypothesis that CJI could be an indicator of further specific severe concomitant injuries. Despite the rather lower relevance of the CJI in the cohort of severely injured with regard to the overall injury severity, these injuries have their importance in relation to the indicator effect for thoracic concomitant injuries and concomitant injuries of the upper extremity. A limitation is the collective registration of SCJ and ACJ injuries as one entity in the TR-DGU. A distorted picture of the CJI in favor of ACJ injuries could arise from the significantly higher incidence of the ACJ dislocation compared to the SCJ. Therefore, these two injury entities should be recorded separately in the future, and prospective studies should be carried out in order to derive a standardized treatment strategy for the care of severely injured with the respective CJI.
CRIS-Team Scopus Importer:2020-12-25

Age Distribution and Concomitant Injuries in Pulmonary Contusion: An Analysis Based on Routine Data - Finkbeiner, Rebekka; Krinner, Sebastian; Langenbach, Andreas; Besendörfer, Manuel; Schulz-Drost, Stefan (Thoracic and Cardiovascular Surgeon, 2018)
BACKGROUND: As the population ages, low-energy thoracic injuries are becoming increasingly relevant in individual injuries, particularly pulmonary contusions (PCs) and their common concomitant injuries. The objective of this study was to determine the prevalence and age distribution of thoracic trauma, especially PC, to make conclusions about common secondary diagnoses and developments in management. METHODS: A retrospective analysis of 209,820 cases, based on German routine data from the years 2009 to 2015, with a main diagnosis (MD) or secondary diagnosis (SD) of thoracic trauma (S27 according to ICD-10) was performed. The entire patient collective with a MD of S27 was examined as well as those with PCs (S27.31). RESULTS: In all 61,016 patients with a MD of S27, 7,558 (12.4%) had a MD of PC and among the 148,804 patients with a SD of S27, 58,247 patients (39.1%) had a SD of PC. PC occurs mostly in the age groups of 20 to 25, 45 to 50, and 70 to 75 years. The proportion of older people tends to be increasing. The most concomitant thoracic injuries were serial rib fractures (27.1%), pneumothorax (11.9%), and sternum fractures (6.2%). Computed tomography scan is the most common diagnostic tool in PC (MD >80%, SD >60%). Therapeutically, intensive care (>50%) and chest drainage are most important (MD: 12.5%, SD: 60.1%), while operative measures are rare (≤ 4%). CONCLUSION: PC shows a marked increase in the incidence, especially in older patients and as a companion diagnosis in thoracic injuries. It should be diagnosed early as well as its concomitant injuries to avoid complications.
EVALuna2:35788

Antibacterial Effect of a 4x Cu-TiO2 Coating Simulating Acute Periprosthetic Infection-An Animal Model - Mauerer, Andreas; Stenglein, Stefanie; Schulz-Drost, Stefan; Schoerner, Christoph; Taylor, Dominic; Krinner, Sebastian; Heidenau, Frank; Adler, Werner; Forst, Raimund (Molecules, 2017)
The purpose of our study was to investigate the antibacterial effect of a spacer (Ti6Al4V) coated with 4x Cu-TiO? in an animal model simulating an acute periprosthetic infection by Staphylococcus aureus. Ti6Al4 bolts contaminated with Staphylococcus aureus were implanted into the femoral condyle of rabbits (n = 36) divided into 3 groups. After one week in group 1 (control) the bolts were removed without any replacement. In group2 Ti6Al4V bolts with a 4x Cu-TiO? coating and in group 3 beads of a gentamicin-PMMA chain were imbedded into the borehole. Microbiological investigation was performed at the primary surgery, at the revision surgery and after scarification of the rabbits 3 weeks after the first surgery. Blood tests were conducted weekly. The initial overall infection rate was 88.9%. In group 2 and 3 a significant decrease of the infection rate was shown in contrast to the control group. The C-reactive protein (CRP) levels declined one week after the first surgery except in the control group where the CRP level even increased. This is the first in vivo study that demonstrated the antibacterial effects of a fourfold Cu-TiO? coating. For the future, the coating investigated could be a promising option in the treatment of implant-associated infections.
EVALuna2:15853

Combined Disruption of the Thoracic Spine and Costal Arch Fracture: An Indicator of a Severe Chest Trauma - Schulz-Drost, Stefan; Kloesel, Stephan; Kuehling, Jan Carsten; Ekkernkamp, Axel; Bakir, Mustafa Sinan (Diagnostics, 2022)
Blunt high-energy chest trauma is often associated with thoracic and abdominal organ injuries. Literature for a hyperextension-distraction mechanism resulting in a costal arch fracture combined with a thoracic spine fracture is sparse. A 65-year-old male suffered a fall from a height of six meters. Initial X-ray of the chest shows left-sided high-riding diaphragm and CT scan proves anterior cartilage fracture, posterolateral serial rib fractures, traumatic intercostal pulmonary hernia, avulsion of the diaphragm, and 7th thoracic vertebral fracture. An exploratory thoracotomy was performed and the rupture of the diaphragm, creating a two-cavity injury, had been re-fixed, the pulmonary hernia was closed, and locking plate osteosyntheses of the fractured ribs including the costal arch were performed. We generally recommend surgical therapy of the thorax to restore stability in this severe injury entity. The spine was fixed dorsally using a screw-rod system. In conclusion, this thoracovertebral injury entity is associated with high overall injury severity and life-threatening thoracoabdominal injuries. Since two-cavity traumata and particularly diaphragmatic injuries are often diagnosed delayed, injuries to the costal arch can act as an indicator of severe trauma. They should be detected through clinical examination and assessment of the trauma CT in the soft tissue window.
CRIS-Team Scopus Importer:2022-10-07
Keywords: costal arch fracture; indicator injury; intercostal hernia; severely injured; thoracic spine fracture

Comparative studies of different types of osteosynthesis on the human corpse preparation in bilateral antero-lateral flail chest - Grupp, Sina; Fürst, Veronika; Buder, Thomas; Fichte, Alexander; Krinner, Sebastian; Carbon, Roman T.; Hennig, Friedrich; Langenbach, Andreas; Schulz-Drost, Stefan (Injury-International Journal of the Care of the Injured, 2017)
Bilateral flail chest injuries are challenging in treatment and comparatively often require an operative stabilization of the anterior chest wall to re-establish normal physiological conditions of the chest wall in shape and statics. Various procedures have been described which are technically sophisticated for the surgeon. Consequently there is an increasing interest in potentials of operative care and their effectiveness on the anterolateral chest wall.12 Human cadavers were prepared and the natural Sternum Position (NP) was marked. A digital probe was fixed to the sternum at the height of the 4th intercostal space in order to measure and compare the stability of the thorax. Readings were taken of the sternal displacement at 1-5cm sagittal distance from NP in starting conditions and from every combination of materials. Serial osteotomies were performed on 2 locations on ribs 2-8 to induce bilateral flail chest. Afterwards the stabilization was achieved with different implants: RESULTS: The osteotomies lead to a subsidence of the sternum occurred to almost 75 mm from NP which corresponds to a maximal unstable situation. The unstable chest wall showed substantially more stabilization through the use of locking plates. Our materialcombinations showed a stability of up to 60% of normal. The more ribs were treated osteosynthetically, the higher the stability of the chest wall.Locking plate fixation offers anatomically realignment of the ribs whereas metal strut support only lifts up the chest wall, but could not provide realignment of the dislocated ribs.
EVALuna2:15857

Concomitant Sternal Fracture in Flail Chest: An Analysis of 21,741 Polytrauma Patients from the TraumaRegister DGU® - Schulz-Drost, Stefan; Krinner, Sebastian; Langenbach, Andreas; Oppel, Pascal; Lefering, Rolf; Taylor, Dominic; Hennig, Friedrich; Mauerer, Andreas (Thoracic and Cardiovascular Surgeon, 2017)
Background Isolated sternal fractures (SFs) rarely show complications, but their influence in a thorax trauma of the seriously injured still remains unclear. Methods A retrospective analysis of the TraumaRegister DGU® was performed involving the years 2009 to 2013 (Injury Severity Score [ISS] >= 16, primary admission to a trauma center). Cohort formation: Unilateral and bilateral flail chest (FC) injuries with and without a concomitant SF, respectively. Results In total, 21,741 patients (25% female) met the inclusion criteria, with 3,492 (16.1%) showing SF. Unilateral FC patients were on average 53.6 ± 18.4 years old, and bilateral FC patients were on average 55.2 ± 17.7 years old. The ISS in unilateral FC and bilateral FC amounted to 31.2 ± 13.0 and 43.4 ± 13.1 points, respectively. FC with an SF occurred more frequently as an injury to car occupants and less frequently as an injury to motorcyclists or in injuries due to falls. Conclusion Patients with an SF additional to an FC had longer hospital and intensive care unit stays and were longer artificially respirated than those patients without an SF. SF indicates possible cardiac and thoracic spine injuries.
EVALuna2:15854

CPR related injuries of the chest wall: direct and indirect fractures - Schenderlein, Anne; Groh, Johannes; Kern, Florian; Perl, Mario; Schulz-Drost, Stefan (European Journal of Trauma and Emergency Surgery, 2025)
BACKGROUND: Rib and sternum fractures are common injuries associated with cardiopulmonary resuscitation (CPR). The fracture mechanism is either direct by application of force on sternum and anterior ribs or indirect by bending through compression of the thorax. The aim of this study was to determine morphologies of rib fractures after CPR and to reevaluate prior findings on fracture localisation, type and degree of dislocation. METHODS: The present study was based on all inpatients treated for chest wall fractures after non traumatic cardiac arrest at a Level 1 Trauma Centre from 2010 to 2016 who had received CT scans. Each fracture was analyzed for location, degree of dislocation and fracture type classified according to AO/OTA and CWIS. We also analysed Fracture Line orientation. RESULTS: We enrolled 40 patients with a total of 423 rib fractures. We found most fractures anterolaterally between the 3rd to 6th rib symmetrically on both sides of the thorax. We found sternum fractures in 30% of the patients, 50% being located at the at the corpus sterni between rib 3 and 4. All patients with sternum fractures suffered from rib fractures and most had fractures of the cartilage or osteochondral junction. All cartilage fractures were straight, undisplaced type A fractures. Most indirect fractures occurred anterolaterally between 50 and 60° in the axial plane. More than 90% of those fractures were classified as type A, 70% showed a straight fracture line and 60% were undisplaced. There was no difference in degree of dislocation between straight and oblique fracture lines. We found 143 incomplete fractures. CONCLUSION: We confirmed prior findings regarding fracture patterns in CPR related injuries. We observed approximately 2-3 times as many straight-lined fractures as oblique ones following indirect trauma. One third of all fractures are incomplete, these highlights the special characteristics like high elasticity of ribs.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Chest wall injury; CPR; Flail chest; Fracture morphology; Indirect fractures; Rib fractures

Do low profile implants provide reliable stability in fixing the sternal fractures as a "fourth vertebral column" in sternovertebral injuries? - Krinner, Sebastian; Grupp, Sina; Oppel, Pascal; Langenbach, Andreas; Hennig, Friedrich; Schulz-Drost, Stefan (Journal of Thoracic Disease, 2017)
Flexion and compression forces to the trunk can cause severe instability of the vertebral column and the anterior chest wall, mostly associated with an unstable fracture of the sternum. In combination, the worst case would be a complete disruption of the trunk. Some authors consider the sternum-rib-complex to be the fourth vertebral column. This study discusses the possibilities to treat instable trunk injuries with sternal fractures concomitant to vertebral spine fractures through anterior sternal plating employing a locked plate osteosynthesis in a low profile design instead of the use of bulky implants.11 Patients suffering from at least one fracture of a vertebral body in combination with an unstable sternum fracture were stabilized through a locked plate osteosynthesis in low profile design at the sternum between November 2011 and October 2014. The vertebral spine injury was stabilized as well, if necessary. Patients were followed up with a look at the consolidation of the fractures and the question if any failure of the implants occurred.Anterior sternal plating was uneventful in all cases. All Sternal fractures showed sufficient consolidation. No failure of implants has been seen during follow up over two years..A locked plate osteosynthesis of a sternal fracture in low profile design seem to be an appropriate option for stabilization of the sternum in combined sternovertebral injuries.
EVALuna2:15858

Do we have to redefine type B-fractures of the rib cartilage? - Groh, Johannes; Kern, Florian; Perl, Mario; Schulz-Drost, Stefan (European Journal of Trauma and Emergency Surgery, 2024)
Objectives: Aim of this work was the evaluation and validation of the AO/OTA classification of the anterior chest wall, here especially for the rib cartilage. Methods: Study design was a retrospective analysis of patients who were hospitalized with fractures of the thoracic wall in the years 2010–2016. This resulted in a collective of n = 124 patients. All fractures of the anterior chest wall were classified according to their location, dislocation and fracture type according to the AO classification. An analysis of possible subtypes was carried out. Results: 29.0% (36) of the patients had fractures of the rib cartilage. 23 of the 36 (64%) patients had multiple fractures, the total number of single fractures amounted to 94. 53.2% (50) of these fractures were in the right hemithorax, 46.8% (44) in the left hemithorax. 95.7% (90) of the fractures were A-fractures, 4.3% (4) were C-fractures. There were no B fractures. The C fractures also consisted exclusively of A fractures (AA fractures). 59.6% (56) of the fractures showed a dislocation. 30.9% (29) were avulsion fractures of either the osteochondral (22.3% (21)) or the sternocostal junction (8.5% (8)). Discussion and conclusion: The costal cartilage obviously does not show typical B fractures as we know them from shaft fractures of long bones. We have compiled a structured analysis in the attached manuscript and validated the classification proposal. In conclusion, we propose an adaptation of the classification proposal based on our data with redefining type B fractures as fractures of the osteochondral joints.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Anterior rib; AO/OTA classification; Costal cartilage; Costochondral; Rib cartilage; Rib fracture; Sternocostal

Effect of surgical stabilization of rib fractures in polytrauma: an analysis of the TraumaRegister DGU(R) - Becker, Lars; Schulz-Drost, Stefan; Spering, Christopher; Franke, Axel; Dudda, Marcel; Lefering, Rolf; Matthes, Gerrit; Bieler, Dan (European Journal of Trauma and Emergency Surgery, 2022)
Purpose In severely injured patients with multiple rib fractures the beneficial effect of surgical stabilization is still unknown. The existing literature shows divergent results and especially the indication and the right timing of an operation are subject of a broad discussion. The aim of this study was to determine the influence of a surgical stabilization of rib fractures (SSRF) on the outcome in a multi-center database with special regard to the duration of ventilation, intensive care and overall hospital stay. Methods Data from the TraumaRegister DGU(R) collected between 2008 and 2017 were used to evaluate patients over 16 years with severe rib fractures (AIS >= 3). In addition to the basic comparison a matched pair analysis of 395 pairs was carried out in order to find differences and to increase comparability. Results In total 483 patients received an operative treatment and 29,447 were treated conservatively. SSRF was associated with a significantly lower mortality rate (7.6% vs. 3.3%, p = 0.008) but a longer ventilation time and longer stay as well as in the intensive care unit (ICU) as the overall hospital stay. Both matched pair groups showed a good or very good neurological outcome according to the Glasgow Outcome Scale (GOS) in 4 of 5 cases. Contrary to the existing recommendations most of the patients were not operated within 48 h. Conclusions In our data set, obviously most of the patients were not treated according to the recent literature and showed a delay in the time for operative care of well over 48 h. This may lead to an increased rate of complications and a longer stay at the ICU and the hospital in general. Despite of these findings patients with operative treatment show a significant lower mortality rate.
CRIS-Team WoS Importer:2022-02-18

Elastic stable chest repair and its hybrid variants in 86 patients with pectus excavatum - Schulz-Drost, Stefan; Luber, Anna Maria; Simon, Kirsten; Schulz-Drost, Melanie; Syed, Julia; Carbon, Roman T.; Besendörfer, Manuel (Journal of Thoracic Disease, 2018)
Background: Complex and mature funnel chest deformities are traditionally managed with open surgical procedures. Elastic stable chest repair (ESCR) has been used successfully and safely for relapse corrections. Does pure plate osteosynthesis in ESCR allow comparable corrective potency and implant safety as hybrid methods with metal bars? Methods: Data from 86 patients with open funnel chest correction between 2011 and 2015 were analyzed in this retrospective study. Exclusion criteria included being under 12 years of age, and having a history of septic wound healing disorder or other malignant diseases. Main groups consisted of ESCR and hybrid techniques, subgroups were primary and recurrence correction. Correction results and follow-up examinations at six and 12 weeks and at 1 year were statistically analyzed. Results: A total of 38 ESCR and 48 hybrid methods were analyzed. Bar implantation was required in 77% (recurrence 34%) of patients. All patients received plates with different combinations e.g., longitudinal-sternal, costosternal and costo-sterno-costal. In all groups, follow-up uptake showed a funnel chest correction result at the anatomical level with healthy values according to the Haller index (ESCR 4.36-2.84, hybrid 6.99-2.74, P<0.001). No material dislocations were observed in any subgroup. Conclusions: ESCR and hybrid techniques represent promising and safe therapeutic approaches.
EVALuna2:35789

Erroneous Classification and Coding as a Limitation for Big Data Analyses: Causes and Impacts Illustrated by the Diagnosis of Clavicle Injuries - Raché, Robert; Claudé, Lara Sophie; Vollmer, Marcus; Haralambiev, Lyubomir; Gümbel, Denis; Ekkernkamp, Axel; Jordan, Martin; Schulz-Drost, Stefan; Bakir, Mustafa Sinan (Diagnostics, 2025)
Background/Objectives: Clavicle injuries are common and seem to be frequently subject to diagnostic misclassification. The accurate identification of clavicle fractures is essential, particularly for registry and Big Data analyses. This study aims to assess the frequency of diagnostic errors in clavicle injury classifications. Methods: This retrospective study analyzed patient data from two Level 1 trauma centers, covering the period from 2008 to 2019. Included were cases with ICD-coded diagnoses of medial, midshaft, and lateral clavicle fractures, as well as sternoclavicular and acromioclavicular joint dislocations. Radiological images were re-evaluated, and discharge summaries, radiological reports, and billing codes were examined for diagnostic accuracy. Results: A total of 1503 patients were included, accounting for 1855 initial injury diagnoses. In contrast, 1846 were detected upon review. Initially, 14.4% of cases were coded as medial clavicle fractures, whereas only 5.2% were confirmed. The misclassification rate was 82.8% for initial medial fractures (p < 0.001), 42.5% for midshaft fractures (p < 0.001), and 34.2% for lateral fractures (p < 0.001). Billing codes and discharge summaries were the most error-prone categories, with error rates of 64% and 36% of all misclassified cases, respectively. Over three-quarters of the cases with discharge summary errors also exhibited errors in other categories, while billing errors co-occurred with other category errors in just over half of the cases (p < 0.001). The likelihood of radiological diagnostic error increased with the number of imaging modalities used, from 19.7% with a single modality to 30.5% with two and 40.7% with three. Conclusions: Our findings indicate that diagnostic misclassification of clavicle fractures is common, particularly between medial and midshaft fractures, often resulting from errors in multiple categories. Further prospective studies are needed, as accurate classification is foundational for the reliable application of Big Data and AI-based analyses in clinical research.
CRIS-Team Scopus Importer:2025-01-31
Keywords: AI-based analyses; big data analyses; clavicle fractures; clavicle injuries; misclassification

From pullout-techniques to modular elastic stable chest repair: the evolution of an open technique in the correction of pectus excavatum - Schulz-Drost, Stefan; Syed, Julia; Luber, Anna-Maria; Carbon, Roman T.; Besendörfer, Manuel (Journal of Thoracic Disease, 2019)
Background: Traditionally open procedures have been replaced by minimally invasive techniques in the correction of pectus excavatum. Efforts to improve the extent of mobilization of the chest wall and its stabilization have led to constant modifications. There is currently no consensus about the best procedure for correction of pectus excavatum.
CRIS-Team WoS Importer:2019-08-13

Indication and results of surgical treatment of rib fractures Indikation und Ergebnisse der operativen Therapie von Rippenfrakturen - Schulz-Drost, Stefan; Krinner, S.; Langenbach, A. (Atemwegs- und Lungenkrankheiten, 2019)
Surgeons have been dealing with rib fractures and their adequate therapy for a long time. Severe pain and possible respiratory insufficiency are immediate risks, remaining deformities are long-term complications, especially in the context of multiple fractures series. Surgical stabilization of rib fractures is indicated for higher-grade instability associated with respiratory failure, persistent deformity, persistent instability, prolonged pain, lack of rib consolidation, and thoracot-omy for other indications, e.g., in the context of surgical intrathoracic injuries such as lung injuries, pneumothorax, or hematothorax. Locked plates are most commonly used for osteosynthesis, with good results and high patient safety. Muscle-sparing, limited access routes with reduced invasiveness have become established, whereas thoracoscopic-assisted procedures are less frequently performed.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Flail chest; Locked plate osteosynthesis; Osteosynthesis; Rib fracture; Sternum fracture; Surgical approach; Unstable chest wall injury

Injuries of the Medial Clavicle: A Cohort Analysis in a Level-I-Trauma-Center. Concomitant Injuries. Management. Classification - Bakir, Mustafa Sinan; Merschin, David; Unterkofler, Jan; Guembel, Denis; Langenbach, Andreas; Ekkernkamp, Axel; Schulz-Drost, Stefan (Chirurgia, 2017)
Introduction: Although shoulder girdle injuries are frequent, those of the medial clavicle are widely unexplored. An applied classification is less used just as a standard management. Methods: A retrospective analysis of medial clavicle injuries (MCI) during a 5-year-term in a Level-1-Trauma-Center. We analyzed amongst others concomitant injuries, therapy strategies and the classification following the AO standards. Results: 19 (2.5%) out of 759 clavicula injuries were medial ones (11 A, 6 B and 2 C-Type fractures) thereunder 27,8% were displaced and thus operatively treated Locked plate osteosynthesis was employed in unstable fractures and a reconstruction of the ligaments at the sternoclavicular joint (SCJ) in case of their disruption. 84,2% of the patients sustained relevant concomitant injuries. Numerous midshaft fractures were miscoded as medial fracture, which limited the study population. Conclusions: MCI resulted from high impact mechanisms of injury, often with relevant dislocation and concomitant injuries. Concerning medial injury's complexity, treatment should occur in specialized hospitals. Unstable fractures and injuries of the SCJ ligaments should be considered for operative treatment. Midshaft fractures should be clearly distinguished from the medial ones in ICD-10-coding. Further studies are required also regarding a subtyping of the AO classification for medial clavicle fractures including ligamental injuries.
EVALuna2:15850

Injuries of the Sternoclavicular Joint - An Innovative Approach in the Management of a Rare Injury: Tight Rope Fixation of the Costo-Clavicular Ligament - Unterkofler, Jan; Merschin, David; Langenbach, Andreas; Ekkernkamp, Axel; Schulz-Drost, Stefan (Chirurgia, 2017)
Background: The costoclavicular ligament (CCL) provides the most tight stability within the sternoclavicular joint (SCJ), followed by the most cited sternoclavicular ligaments (SCL). Their disruption may cause severe instability of the SCJ. Different treatment options, such as the use of plates, wires or autologous tendons are associated with mainly limited functional outcome. Could a stabilization of CCL next to an anatomic fixation of the SCL provide sufficient reconstruction of the SCJ? Methods: A 58-year-old male showed severe anterior and painful instability of the SCJ following a fall on his shoulder 8 weeks ago. The SCJ had been reconstructed in an open procedure with stabilization of the CCL employing 2 tight ropes and anatomical suture of the SCL. Follow-up was carried out 78 weeks after operation. Results: The reduction of the SCJ was successful. X-ray proved the anatomic position of the SCJ. Pain was decreased in between the first 6 weeks. The patient showed uneventful follow-up and returned to work 6 months after the procedureas a hard working farmer. Conclusions: Innovative stabilization of the CCL with tight ropes additional to a suture of the SCL may enable anatomic reconstruction of the SCJ considering cosmetic and functional results.
EVALuna2:15851

Is intrathoracic rib plate fixation advantageous over extrathoracic plating? A biomechanical cadaveric study - Mischler, Dominic; Schopper, Clemens; Gasparri, Mario; Schulz-Drost, Stefan; Brace, Michael; Gueorguiev, Boyko (Journal of Trauma and Acute Care Surgery, 2022)
BACKGROUND: The high morbidity following surgical interventions on the chest wall because of large incisions often prevents surgeons from operative rib fracture treatment. Minimally invasive approaches to the intrathoracic side of the rib could allow for smaller incisions with lower morbidity while maintaining stability of fixation. The aim of this study was to explore the biomechanical competence of intrathoracic versus extrathoracic plating in a human cadaveric rib fracture model and investigate the effect of plating using two versus three screws per fracture fragment. METHODS: Twenty pairs of fresh-frozen human cadaveric ribs from elderly female donors aged 82.4 ± 7.8 years were used. First, the stiffness of each native rib was calculated via nondestructive (2 N-5 N) biomechanical testing under two loading conditions: ramped two-point bending and combined ramped tensile bending with torsional loading. Second, the ribs were fractured under three-point bending with their intrathoracic side put under tensile stress. Third, specimens were assigned to four groups (n = 10) for either intrathoracic or extrathoracic plating with two or three screws per fragment. Following instrumentation, all ribs were dynamically tested over 400,000 cycles under combined sinusoidal tensile bending with torsional loading (2 N-5 N at 3 Hz). Finally, all specimens were destructively tested under ramped two-point bending. RESULTS: Following instrumentation and cyclic testing, significantly higher construct stiffness was observed for intrathoracic vs. extrathoracic plating under anatomical loading conditions (p ≤ 0.03). No significant differences were detected for implant subsidence after plating with two or three screws per fragment (p ≥ 0.20). CONCLUSION: This study demonstrates significantly higher construct stiffness following intrathoracic over extrathoracic plating, thus indicating superior plate support of the former. In the clinical context, using only two instead of three screws per fragment not only could maintain stability of fixation but also decrease surgery time and costs, and allow for smaller incisions with lower morbidity. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level V.
CRIS-Team Scopus Importer:2022-03-04

Lung Contusion in Polytrauma: An Analysis of the TraumaRegister DGU - Schulz-Drost, Stefan; Finkbeiner, Rebekka; Lefering, Rolf; Grosso, Marco; Krinner, Sebastian; Langenbach, Andreas (Thoracic and Cardiovascular Surgeon, 2021)
Background Thorax trauma frequently occurs in which injuries to the bony chest, lung contusions (LCs), and others are diagnosed. The significance of this violation is described very differently and is mostly based on monocentric data. Methods A retrospective analysis of the TraumaRegister DGU ®(TR-DGU) dataset (Project 2014-062) was performed between 2009 and 2014 (injury severity score [ISS] ≥ 16, primary admission to a trauma center, no isolated traumatic brain injury). Patients with LC (Abbreviated Injury Scale [AIS] 3 + 4) were compared with the control group, and an analysis of different age groups was performed. Results A total of 49,567 patients were included, thereunder 14,521 (29.3%) without relevant thoracic trauma (TT); 95.9% blunt traumas. 18,892 patients (38.1%) had LC and 14,008 (28.3%) had severe LC with AIS 3 + 4; thereunder 72.7% males. For severe LC, the average age was the lowest (44.7 ± 19.7 years) and ISS the highest (30.4 ± 12.1 points). Intubation, intensive care, (multi-) organ failure, sepsis, and extrathoracic injuries were most common in severe LC. Shock, chest tubes, further thoracic injuries, and patient death occurred most frequently in TT without LC.Younger patients showed a higher incidence of LC than the older ones; however, high patient age was a highly significant risk factor for the development of complications and poor outcome. Conclusion Since LC was present in almost 40% of the severely injured and was related to higher morbidity, LC should be detected and managed at the earliest possible time. Proper follow-ups employing chest X-rays and computed tomography (CT) scans are recommended.
CRIS-Team Scopus Importer:2021-12-24
Keywords: chest trauma; lung contusion; Polytrauma; pulmonary contusion; TraumaRegister

Reduced invasive and muscle-sparing operative approaches to the posterolateral chest wall provide an excellent accessibility for the operative stabilization! : Minimized approaches to the posterolateral chest wall - Langenbach, A.; Oppel, Pascal; Grupp, Sina; Krinner, Sebastian; Pachowsky, Milena; Buder, Thomas; Schulz-Drost, Melanie; Hennig, Friedrich; Schulz-Drost, Stefan (European Journal of Trauma and Emergency Surgery, 2017)
Stabilizing techniques for flail chest injuries are described through wide surgical approaches to the chest wall, especially in the most affected posterior and lateral regions. Severe morbidity due to these invasive approaches needs to be considered due to dissection of the scapular guiding muscles and the risk of injuries to neurovascular bundles. This study discusses possibilities for minimized approaches to the posterior and lateral regions.Ten fresh-frozen cadavers in lateral decubitus position were observed on both sides. Each surgical arm was kept mobile during the procedure. Approaches were performed following a standard protocol with muscle-sparing incisions starting with 5 cm in length and extending to 10 and 15 cm. The accessible surface comparing the extensions was measured. Visible ribs were counted. In a next step, MatrixRib® Plates were fixed to those ribs to prove the feasibility of rib stabilization through limited approaches.Combinations of the posterior and lateral minimized approaches allow surgical fixation of 6-9 and 7-11 ribs through 5 and 10 cm incisions, respectively. In the case of an extreme expansion of a rib fracture series, an access extension can be made to 15 cm to be able to adequately supply the entire hemithorax using two approaches.Extensive invasive surgical approaches to the thoracic wall can be replaced by reduced invasive and muscle-sparing access combinations. A free-moving positioning of the arm and an accurate preoperative plan for minimizing approaches are essential. Minimally invasive plate techniques are very helpful adjuncts.
EVALuna2:15855

Shoulder girdle injuries involving the medial clavicle differ from lateral clavicle injuries with a focus on concomitant injuries and management strategies: A retrospective study based on nationwide routine data - Bakir, M. Sinan; Unterkofler, Jan; Hönning, Alexander; Haralambiev, Lyubomir; Kim, Simon; Ekkernkamp, Axel; Schulz-Drost, Stefan (PLoS ONE, 2019)
INTRODUCTION: Although shoulder girdle injuries are frequent, those of the medial part are widely unexplored. Our aim is to improve the knowledge of this rare injury and its management in Germany by big data analysis. METHODS: The data are based on ICD-10 codes of all German hospitals as provided by the German Federal Statistical Office. Based on the ICD-10 codes S42.01 (medial clavicle fracture, MCF) and S43.2 (sternoclavicular joint dislocation, SCJD), anonymized patient data from 2012 to 2014 were evaluated retrospectively for epidemiologic issues. We analyzed especially the concomitant injuries and therapy strategies. RESULTS: A total of 114,003 cases with a clavicle involving shoulder girdle injury were identified with 12.5% of medial clavicle injuries (MCI). These were accompanied by concomitant injuries, most of which were thoracic and craniocerebral injuries as well as injuries at the shoulder/upper arm. A significant difference between MCF and SCJD concerning concomitant injuries only appears for head injuries (p = 0.003). If MCI is the main diagnosis, soft tissue injuries typically occur as secondary diagnoses. The MCI are significantly more often associated with concomitant injuries (p < 0.001) for almost each anatomic region compared with lateral clavicle injuries (LCI). The main differences were found for thoracic and upper extremity injuries. Different treatment strategies were used, most frequently plate osteosynthesis in more than 50% of MCF cases. Surgery on SCJD was performed with K-wires, tension flange or absorbable materials, fewer by plate osteosynthesis. CONCLUSIONS: We proved that MCI are rare injuries, which might be why they are treated by inhomogeneous treatment strategies. No standard procedure has yet been established. MCI can occur in cases of severely injured patients, often associated with severe thoracic or other concomitant injuries. Therefore, MCI appear to be more complex than LCI. Further studies are required regarding the development of standard treatment strategy and representative clinical studies.
CRIS-Team Scopus Importer:2019-11-05

Stabilization of flail chest injuries: minimized approach techniques to treat the core of instability - Schulz-Drost, Stefan; Grupp, Sina; Pachowsky, Milena; Oppel, Pascal; Krinner, S.; Mauerer, A.; Hennig, Friedrich; Langenbach, A. (European Journal of Trauma and Emergency Surgery, 2017)
Stabilizing techniques of flail chest injuries usually need wide approaches to the chest wall. Three main regions need to be considered when stabilizing the rib cage: median-anterior with dissection of pectoral muscle; lateral-axillary with dissection of musculi (mm) serratus, externus abdominis; posterior inter spinoscapular with division of mm rhomboidei, trapezius and latissimus dorsi. Severe morbidity due to these invasive approaches needs to be considered. This study discusses possibilities for minimized approaches to the shown regions.Fifteen patients were stabilized by locked plate osteosynthesis (MatrixRib®) between May 2012 and April 2014 and prospectively followed up. Flail chest injuries were managed through limited incisions to the anterior, the lateral, and the posterior parts of the chest wall or their combinations. Each approach was 4-10 cm using Alexis® retractor.One minimized approach offered sufficient access at least to four ribs posterior and laterally, four pairs of ribs anterior in all cases. There was no need to divide latissimus dorsi muscle. Trapezius und rhomboid muscles were only limited divided, whereas a subcutaneous dissection of serratus and abdominis muscles was necessary. A follow-up showed sufficient consolidation.pneumothorax (2) and seroma (2).Minimized approaches allow sufficient stabilization of severe dislocated rib fractures without extensive dissection or division of the important muscles. Keeping the arm and, thus, the scapula mobile is very important for providing the largest reachable surface of the rib cage through each approach.
EVALuna2:15852

Surgical Stabilization of Costoclavicular Injuries - A Combination of Flail Chest Injuries and a Clavicula Fracture - Langenbach, Andreas; Pinther, Melina; Krinner, Sebastian; Grupp, Sina; Ekkernkamp, Axel; Hennig, Friedrich; Schulz-Drost, Stefan (Chirurgia, 2017)
Background: Flail chest injuries (FCI) are associated with a high morbidity and mortality rate. As a concomitant clavicle fracture in FCI even worsens the outcome, the question is how can those costoclavicular injuries (CCI) be managed surgically. Methods: 11 patients with CCI were surgically treated by a locked plate osteosynthesis of the Clavicle and the underlying ribs through limited surgical approaches under general anesthesia. Patients were followed up after 2, 6, 12, 26 and 52 weeks. Results: All patients showed severe chest wall deformity due to severely displaced fractures of the ribs and the clavicle. They were suffering from pain and restriction of respiratory movements. The chest wall could be restored to normal shape in all cases with uneventful bone healing and a high patient convenience. Fractures of the clavicle and the second rib were managed through an innovative clavipectoral approach, the others through standard approaches to the anterolateral and the posterolateral chest wall. Two patients complained about numbness around the lateral approach and lasting periscapular pain. Conclusions: Surgical stabilization might be the appropriate therapy in CCI with dislocated fractures since they would cause severe deformity and loss of function of the chest wall and the shoulder.
EVALuna2:15848

Symptoms in Pectus Deformities: A Scoring System for Subjective Physical Complaints - Ewert, Franziska; Syed, Julia; Kern, Sonja; Besendörfer, Manuel; Carbon, Roman T.; Schulz-Drost, Stefan (Thoracic and Cardiovascular Surgeon, 2017)
Background The literature is silent on the relationship between symptoms and the Haller index. Nor is there a classification of the severity of the physical complaints. Materials and Methods Retrospectively, data from 128 patients (102 funnel, 25 pigeon chest patients, and 1 mixed type) were evaluated. To objectify the symptoms, we developed a score to describe the level of physical ailments. This score includes 10 different symptoms as well as the situation or frequency in which they occur and an impact factor. This depends on how much they affect everyday life. Results Pectus excavatum patients express physical complaints more frequently than pectus carinatum patients who actually suffer more from psychological stress. We could not find a correlation between the Haller index and symptoms or levels of ailment. Conclusion Pectus deformities are likely to cause physical and psychological complaints. Since the subjective symptoms did not show any correlation to the chest severity index, they are supposed to be independent from the deformity's extent.
EVALuna2:35787

Taxonomy of multiple rib fractures: Results of the chest wall injury society international consensus survey - Edwards, John G.; Clarke, Peter; Pieracci, Fredric M.; Bemelman, Mike; Black, Edward A.; Doben, Andrew; Gasparri, Mario; Gross, Ronald; Jun, Wu; Long, William B.; Lottenberg, Lawrence; Majercik, Sarah; et al. (Journal of Trauma and Acute Care Surgery, 2020)
CRIS-Team Scopus Importer:2020-02-18

The Operative Management of Flail Chest Injuries with Concomitant Sternal Fracture - Schulz-Drost, Stefan; Krinner, Sebastian; Langenbach, Andreas; Merschin, David; Grupp, Sina; Hennig, Friedrich; Ekkernkamp, Axel; Mauerer, Andreas (Chirurgia, 2017)
Background: Flail Chest Injuries (FCI) are one of the most severe thoracic injuries. Moreover, an additional sternal fracture (SF) even worsens the outcome, such as the duration of mechanical ventilation, therefore an surgical fixation of the fractures could be considered in certain cases to improve the weaning from the ventilator. This paper aims to emphasize on the management of different types of SF in FCI. Methods: All surgically treated cases (2012-2016) that showed the combination of FCI and SF have been evaluated for their clinical details, the morphology of the fractures and the technical aspects of the surgical procedure in a retrospective investigation. Results: All of the SF (n=15) had been fixed by locked plate osteosynthesis through a median approach in a supine position. Three main regions of the sternum showed the need for different fixation strategies: the upper manubrium, central and lower corpus sterni. Concomitant rib fractures were addressed either through the same approach or through additional limited incisions. Conclusions: Combinations of SF and FCI are high risc injuries with high demand on surgical skills. They can be properly fixed with a locking plate osteosynthesis through a combination of limited incisions employing different types of plates depending on the type of SF.
EVALuna2:15849

The significance of a concomitant clavicle fracture in flail chest patients: incidence, concomitant injuries, and outcome of 12,348 polytraumata from the TraumaRegister DGU® - Bakir, Mustafa Sinan; Langenbach, Andreas; Pinther, Melina; Lefering, Rolf; Krinner, Sebastian; Grosso, Marco; Ekkernkamp, Axel; Schulz-Drost, Stefan (European Journal of Trauma and Emergency Surgery, 2021)
Purpose: Isolated clavicle fractures (CF) rarely show complications, but their influence in the thorax trauma of the seriously injured still remains unclear. Some authors associate CF with a higher degree of chest injuries; therefore, the clavicle is meant to be a gatekeeper of the thorax. Methods: A retrospective analysis of the TraumaRegister DGU® (project 2017-10) was carried out involving the years 2009–2016 (ISS ≥ 16, primary admission to a trauma center). Cohort formation: unilateral and bilateral flail chest injuries (FC), respectively, with and without a concomitant CF. Results: 73,141 patients (26.5% female) met the inclusion criteria and 12,348 had flail chest injuries (FC; 20.0% CF; 67.7% monolateral FC), 25,425 other rib fractures (17.7% CF), and 35,368 had no rib fractures (6.5% CF). On average, monolateral FC patients were 56.0 ± 17.9 years old and bilateral FC patients were 57.7 ± 19 years old. The ISS in unilateral and bilateral FC were 29.1 ± 11.7 and 42.2 ± 12.9 points, respectively. FC with a CF occurred more frequently with bicycle and motorbike injuries in monolateral FC and pedestrians in bilateral FC injuries and less frequently due to falls. Patients with a CF in addition to a FC had longer hospital and ICU stays, underwent artificially respiration for longer periods, and died less often than patients without a CF. The effects were highly significant in bilateral FC. CF indicates more relevant concomitant injuries of the lung, scapula, and spinal column. Moreover, CF was associated with more injuries of the extremities in monolateral CF. Conclusion: Due to the relevance of a concomitant CF fracture in FC, diagnostics should focus on finding CFs or rule them out. Combined costoclavicular injuries are associated with a significantly higher degree of thoracic injuries and longer hospital stays.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Clavicle fracture; Costoclavicular injury; Flail chest; Trauma registry